Development of STREAM-Based Student Worksheets for Teaching Fluid Dynamics at SMAN 14 Medan - Putri Aprillia; Juniar Hutahaean (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The low learning outcomes of students in dynamic fluid material and the limited use of innovative instructional materials necessitate the development of learning tools that integrate 21st-century skills. This study aims to develop a Student Worksheet based on the STREAM approach that is valid, practical, and effective for Grade XI MIPA students at SMAN 14 Medan. This research employed the Research and Development (R&D) method using the 4-D model, consisting of define, design, develop, and disseminate stages. The research subjects were 36 students of class XI MIPA 3 at SMAN 14 Medan. The research instruments included expert validation sheets, a teacher response questionnaire using a Likert scale, a student response questionnaire using a Guttman scale, and a pretest-posttest assessment. Data were analyzed using Likert and Guttman scales to determine validity and practicality, and the N-Gain test to measure effectiveness. The results showed that the LKPD was highly valid, obtaining 97.90% from the material expert and 87.78% from the media expert. Practicality results indicated 93.22% from student responses and 100% from the physics teacher, both categorized as highly practical. The effectiveness test showed an N-Gain score of 0.89 (89%), indicating that the LKPD was highly effective. It can be concluded that the developed LKPD meets the criteria of being highly valid, practical, and effective, and can serve as an alternative instructional material in physics learning. Furthermore, it enhances students’ learning outcomes while facilitating critical thinking, problem-solving skills, and interdisciplinary integration through the STREAM approach.